PENGARUH BRAND IMAGE, FASILITAS BELAJAR, DAN BIAYA PENDIDIKAN TERHADAP KEPUTUSAN MAHASISWA MEMILIH PROGRAM STUDI AKUNTANSI SYARIAH FAKULTAS EKONOMI DAN BISNIS ISLAM IAIN METRO - Lella Anita; Berwin Anggara (BADAN PENERBIT STIEPARI PRESS, 2022)
The research of this study was to provide empirical evidence of the influence of brand image, learning facilities, and education costs on students' decisions to choose the Sharia Accounting Study Program, Faculty of Islamic Economics and Business, IAIN Metro. This study uses a quantitative descriptive method. The population in this study were sharia accounting students at the Faculty of Islamic Economics and Business, IAIN Metro, 2022/2023, with a total of 100 people. Sampling using purposive sampling method. The analysis technique used is the Structural Equation Model (SEM) using the Partial Least Square (PLS) application program version 3.0.m. The results of this study indicate that (1) Brand image has a positive and significant effect on student decisions in choosing the FEBI IAIN Metro accounting study program. (2) Learning facilities have no significant positive effect on student decisions in choosing the FEBI IAIN Metro accounting study program. (3) Brand image has a significant effect on student decisions in choosing the FEBI IAIN Metro accounting study program.